Bone Mineral Density Screening and the Frequency of Osteopenia/Osteoporosis in Turkish Adult Patients with Celiac Disease - Al-Mendalawi, Mahmood D. (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Al-Mendalawi MD. Bone mineral density screening and the frequency of osteopenia/osteoporosis in Turkish adult patients with celiac disease. Turk J Gastroenterol. 2022;33(5):453.